2015
DOI: 10.1515/joepi-2015-0032
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of epilepsy – consequences for work and professional activities

Abstract: Summary Introduction. The correct diagnosis of epileptic seizures and non-epileptic attacks has a decisive influence on treatment, counseling and duration of possible work limitations. Diagnostic efforts should aim towards classifying the seizure as precisely as possible. For risk assessments, e.g. at the workplace, a close cooperation and networking of all professionals involved in the epilepsy treatment, care and consultation processes is required. Aim. To present guidelines for assessment of occupational ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Thus, at best, there is no difference between the employment rates of people with epilepsy and controls. The employment rate of 70% can be maintained among adults with onset of epilepsy when in working life through preventive and rehabilitation measures [86]. While the employability rate was significantly lower among subjects than in controls in the study by Sillanpä ä et al [5], Kokkonen et al [80] reported no significant difference in the employability rates between the subjects and controls.…”
Section: Social Integrationmentioning
confidence: 93%
“…Thus, at best, there is no difference between the employment rates of people with epilepsy and controls. The employment rate of 70% can be maintained among adults with onset of epilepsy when in working life through preventive and rehabilitation measures [86]. While the employability rate was significantly lower among subjects than in controls in the study by Sillanpä ä et al [5], Kokkonen et al [80] reported no significant difference in the employability rates between the subjects and controls.…”
Section: Social Integrationmentioning
confidence: 93%